(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Diseases of the gallbladder (GB) and biliary tract (GDT) are a very pressing problem for modern medicine, due to their extremely wide prevalence and great difficulties for clinicians in differentiated recognition and treatment of this pathology. In the overall structure of gastroenterological morbidity, they account for more than 40% and have a clear tendency towards progressive growth. Currently, in Russia, the incidence of gallbladder and gallbladder pathology ranges from 29.4 to 45.5 cases per 1000 adult population, and in most cases, loss of ability to work occurs many times during the year. Chronic acalculous cholecystitis (CAC) occupies a central place among biliary pathologies, diagnosed in 55-63% of cases. Timely diagnosis of chronic bile duct disease with recognition of the biliary dysfunctions that invariably accompany it is a necessary guarantee of the effectiveness of individual etiotropic treatment of patients. However, the treatment of chronic biliary tract and dysfunctional disorders is not a solved problem for clinicians, since the diagnostic techniques used do not allow one to clearly differentiate the pathology of the biliary tract.Among the large arsenal of laboratory and instrumental research methods, the method of fractional duodenal intubation (FDS) with subsequent study of the physico-chemical composition of bile is a distinctive feature of the entire diagnosis of chronic bile duct disease. This is practically the only method that allows you to objectively assess not only the kinetic ability of the gallbladder and the tone of the sphincter apparatus, but also to identify pathology at the level of changes in the microscopic and biochemical parameters of the resulting bile. The biochemical composition of bile is a highly informative indicator of the state of the hepatobiliary system, allowing one to diagnose not only the stage of the developed disease, but also to identify pre-disease. Mathematical calculation of FDZ graphs using the method of N.G. Kamaeva and M.E. Semendyaeva (1979), significantly improved the diagnostic capabilities of classical duodenal intubation, since the quantitative characteristics of choledynamic processes made it possible to more accurately differentiate various forms of dyskinetic disorders, determine the degree of bile deficiency and differentiate individual pathogenetic therapy.